Somatic embryogenesis, antioxidant metabolism and reserve mobilization during cryopreservation of Passiflora ligularis Juss. zygotic embryos - Prudente, Débora de Oliveira (2017)
Passiflora ligularis Juss. is an endemic species from South America with important medicinal properties. The sexual propagation of P. ligularis present non-uniformity, extended dormancy and your conservation in conventional storage banks is limited by the loss of germination potential. The objectives of this work are obtain plants via somatic embryogenesis from zygotic embryos, characterizing the origin of somatic embryos, and evaluate the influence of exposure time to the cryoprotectant PVS2 on the mobilization of reserves and on antioxidant metabolism during the germination of cryopreserved P. ligularis zygotic embryos. The results demonstrate that the highest frequency of somatic embryo formation was observed on a culture medium supplemented with 27.2 µM 2,4-diclorophenoxyacetic acid + 4.5 µM 6-benzyladenine. The complete independence of somatic embryos from the adjacent tissues was histologically confirmed by the absence of vascular continuity, after 60 days. It was verified an increase in the activity of key enzymes for the glyoxylate cycle, malate synthase (Msy) and isocitrate lyase (ICL), and changes in antioxidant metabolism after exposure of zygotic embryos to 60 min of PVS2 before cryopreservation, accelerating the germination in P. ligularis. This study describes a complete micropropagation route for P. ligularis and moreover shows the precise origin of embryogenic cells. The PVS2 vitrification technique was successfully used to cryopreserve P. ligularis zygotic embryos.